Some Gains from Trade in Producer Goods - Enke, Stephen (Quarterly Journal of Economics, 1961)
Introduction, 635. — Balanced trade in consumer goods, 636. — Balanced trade in consumer goods and producer goods, 637. — Unbalanced but offsetting trade in producer and consumer goods, 639. — A pedagogical comment, 642.